A self-powered and arch-structured triboelectric nanogenerator for portable electronics and human-machine communication. Issue 18 (30th April 2020) - Shi, Xingxing; Zhang, Shuidong; Gong, Shaoqin
Abstract : An arch-structured TENG with a high-power density for portable electronics and self-powered human-machine communication. Abstract : An arch-structured triboelectric nanogenerator (TENG) was developed using nanofibrous poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP) and nylon 6, 6 (PA) membranes as the triboelectric pair and conductive fabrics as the electrodes. The nanofibrous microstructure and tribopolarity differences between the two triboelectric layers endow the TENG with outstanding triboelectric output performances, including an open-circuit voltage of 141.6 V and a short-circuit current of 20.4 μA. A maximum power density of 31.96 W m −2 was achieved at a load resistance of 10 6 Ω. The arch-structured TENG with such a high-power density has the ability to power portable small electronics, such as light-emitting-diodes (LEDs), liquid crystal displays (LCDs) and calculators. A self-powered sensing system was also fabricated using an arch-structured TENG and a signal processing circuit. The self-powered sensing system can readily detect the triboelectric signal generated by finger pressing and can effectively switch small electronics ( e.g., an LED and a small motor) on and off. In addition, a TENG-based calculator was fabricated using 16 separate arch-structured TENGs that acted as the function keys of the calculator. Through real-time communication between a TENG-based calculator, a signal processing circuit and a computer, the TENG-based calculation system is able to complete the mathematical calculation process after the corresponding function keys were pressed. Therefore, an arch-structured TENG can not only power portable electronics, but also function as self-powered sensors in human-machine communication.